Behavior control of membrane-less protein liquid condensates with metal ion-induced phase separation - Kibeom Hong (Nature Portfolio, 2020)
Mimetic membrane-less organelles are of interest for the range of biochemical processes which can be spatio-temporally organized using them. Here, the authors report on a protein condensate system formed by metal ion induced clustering and demonstrate control over condensate properties.